Efficacy and safety of a smartphone application‐based treatment of ketogenic diet in pediatric refractory epilepsy - Wei Li; Wei Gu; Chao Liang; Fulai Tu; Le Ding; Xiaopeng Lu; Hu Guo; Guo Zheng; Chunfeng Wu (Epilepsia Open, 2024)
Abstract Objective We aimed to find predictors for smartphone application‐based ketogenic diet (KD) treatment effectiveness and safety. Methods The efficacy was evaluated according to the reduction in seizure frequency after the intervention of KD; safety was evaluated based on adverse effects. The ordinal logistic regression analysis was used to explore the influencing factors of efficacy. Results The study sample included 116 males and 65 females with a median age of 2.27 years. The baseline frequency of seizure was more than five times/day in 123 children, 50.83% of them received three or more antiepileptic drugs (AEDs). Seventy‐two patients' KD initiation mode was outpatient, and 73 completed the 12‐month follow‐up. A total of 88 (48.62%) patients had reported a reduction in seizure ≥50%. Compared with 12 months, those who had received KD therapy for only 3 (P = 0.009) and 6 months (P = 0.005) were more likely to show negative outcomes. Outpatient initiation had better outcomes (P = 0.029) than inpatient initiation. For the number of AEDs applied, patients on two AEDs were more likely to achieve better outcomes (P = 0.001). Adverse events had been noted among 77 patients; BMI Z‐score at KD initiation was associated with adverse effects (P = 0.003). Significance Our study suggested that outpatient initiation and long‐term treatment of KD should be encouraged. Plain Language Summary Our research shows that the KD is a helpful treatment for children with refractory epilepsy, reducing seizures by more than 50% in nearly half of the cases, with some experiencing complete seizure freedom. We used a smartphone app to improve communication between patients and their healthcare teams, resulting in a high retention, and app usage was linked to reduced adverse effects. We recommend early consideration of KD treatment for patients failing two AED, encourage outpatient initiation, and advocate for longer‐term KD use.